LEGAL IMPACT ON THE IMPLICATIONS OF THE SUPREME COURT CIRCULAR LETTER NUMBER 3 OF 2023 ON FOREIGN LANGUAGE AGREEMENTS - Alzena Bernadine; Abdul Salam (Faculty of Law, Universitas Pekalongan, 2024)
The obligation to use the Indonesian language in agreements involving Indonesian privateinstitutions and Indonesian citizens, as stipulated in Article 31 of Law No. 24 of 2009on the Flag, Language, and State Emblem, and the National Anthem, in conjunction withPresidential Regulation No. 63 of 2019 on the Use of the Indonesian Language, has sparkedvarious implementation issues. Several court cases have declared contracts made in a foreignlanguage without an Indonesian translation null and void, while others have been upheld.In response to these issues, the Supreme Court of the Republic of Indonesia issued SupremeCourt Circular No. 3 of 2003, which essentiallystates that contracts drafted in a foreignlanguage without an accompanyingIndonesian translation cannot be grounds forannulment unless it can be proven that theabsence of an Indonesian translation was dueto bad faith by one of the parties. This researchexamines the regulation and status of aSupreme Court Circular within the Indonesianlegal system and the legal implications arisingfrom the issuance of SEMA No. 3/2023 oncontracts involving foreign parties that aremade without an Indonesian translation. Thisstudy employs doctrinal research methods,using document studies with secondary data,and utilizes descriptive-analytical researchspecifications, analyzed through qualitative methods. The findings show that SEMA No.3/2023 is not a piece of legislation within thehierarchy of laws but is an internal policyregulation (beleidsregel) that applies onlywithin the internal scope of the judiciary,serving as a guideline for judges and justices incourt rulings. The presence of SEMA No.3/2023 creates legal uncertainty as it conflictswith Article 31 of Law No. 24/2009 and Article26 of Presidential Regulation No. 63/2019,rendering contracts involving Indonesianprivate institutions and Indonesian citizensmade without an Indonesian translation nulland void